Abordagens computacionais aplicadas ao estudo de semicondutores nanoestruturados - Jesus, João Paulo Almirão de (2022)
This thesis is mainly focused on applying different computational methodologies in two case studies, using hexagonal clusters with M6X6 (M = Zn, Cd e X = S, O) configuration as models for ZnS, Zn6-x Cdx S6 , CdS, and ZnO colloidal semiconductors with wurtzite structure. In the first work, it was presented the theoretical study of the effects ofan electric field on the electronic structure and spectroscopic properties ofZn6-x Cdx S 6 clusters. Hence, it was identified distortions in the bond angles and lengths according to the cluster hybridization due to the more compact structure of Zn6 S6 in comparison to Cd6 S6 , while the Zn3 Cd3 S6 cluster was the most distorted, as wellas the Raman active-modes and the thermodynamical properties, suggesting theZn6 S6 clusters as the most stable. Under the effects of an electric field, the distortions in bond angles and lengths increase significantly, reaching alimit at 0.20 V Å-1 , thus observing polarizations in the local structuresand verifying the quantum Stark effect due to energy shifts in the physical properties and the HOMO and LUMO polarizations, keeping a tendency throughout the text. In the second work, a theoretical-experimental approach was taken in the study of ZnS and ZnO compounds in three steps. First, ZnS and ZnO nanoparticles were synthesized by means of the hydro(solvo)thermal route and their structural, spectroscopic, and photocatalytic propertieswere analyzed, showing their excellent ability to degrade methylene blue dye. Second, the ground and excited state structures of Zn6 O 6 and Zn6 S6 were simulated, studying their electronic and vibrational properties and their chemical behavior, in which QTAIM and NBO analyses indicated the higher ionic bond character of ZnO clusters, resulting in a more polarized and distorted structure and, as consequence, intrinsic defects. Lastly, the optimized clusters were submitted to molecular docking study , and their ability to inhibit the proteins of the SARS-CoV-2, Escherichia coli and Fusarium solani were evaluated, suggesting a broad spectrum of antimicrobial activityfor the ZnO and ZnS nanoparticles and elucidating the excited state influence into the higher inhibition activity against pathogenic agents. Hence, in this last study, it was discovered the high reactivity of these particles as disinfectant agents, UVA and UVB blocking ability, and a large spectrum of antimicrobial properties. Therefore, as shown in the results, the computational approaches reached excellent results in both works, always following tendencies and presenting values close to those reported in the literature and within the methodological deviation, highlighting the efficiency of theoretical calculations in the study of functional materials.